PENGARUH INDEPENDENSI, MEKANISME CORPORATE GOVERNANCE, KUALITAS AUDIT, DAN MANAJEMEN LABA TERHADAP INTEGRITAS LAPORAN KEUANGAN - Daniel Salfauz Tawakal Putra Putra; Dul Muid (Diponegoro Journal of Accounting, 2012)
This study aims to analyze and obtain empirical evidence about the effect of independence, corporate governance mechanisms (institutional ownership, managerial ownership, audit committees, independent commissioners), audit quality and earnings management for the integrity of financial statements in manufacturing companies in Indonesia. Integrity of financial statements is defined as the extent to which the financial statements show a true and honest information. Independent variables used in this study is the independence, corporate governance mechanisms are analyzed by institutional ownership, managerial ownership, audit committees, independent commissioners, audit quality and earnings management. Dependent variable used in this study is the integrity of financial statements analyzed by conservatism, in observation from 2008-1010. This study uses 40 manufacturing companies listed on the Stock Exchange in 2008 through 2010. Samples obtained using a purposive sampling method. The research data were analyzed with multiple linear regression analysis. The study is an independent commissioner, managerial ownership and institutional ownership did not significantly affect the integrity of financial statements. As for independence, audit committee, audit quality and earnings management significantly affect the integrity of the financial statements.